QUALITY OF LIFE OF PERSONS WITH TRAUMATIC SPINAL CORD INJURIES - Lionela da Silva Corrêa; David Lopes Neto; Eliana Ofélia Llapa-Rodriguez (Universidade Federal do Paraná, 2015)
This descriptive quantitative study aimed to evaluate the quality of life of persons with traumatic spinal cord injuries attended in a teaching hospital in Manaus, in the Brazilian state of Amazonas, between August and October 2011. A total of 30 paraplegics with traumatic spinal cord injuries participated in the study. The World Health Organization Quality of Life-Bref questionnaire was used for measuring quality of life. This is divided into four domains: physical health, psychological health, social relationships and environment. The results showed a predominance of the male gender, aged between 31 and 45 years old, who had lived with the injury for five to eight years. Of the 30 interviewees, 20% and 36.7% assessed quality of life as 'very good' and 'good' respectively. Among the domains, the psychological, social and environmental stood out, with evaluations of quality of life as good (56.7%), average (43.3%) and average (53.3%). It is concluded that persons with spinal cord injuries perceive themselves as having a satisfactory quality of life in the sets of the psychological and social domains.